2020
DOI: 10.1002/adfm.202004537
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning Multilayered Scaffolds Loaded with Melatonin and Fe3O4 Magnetic Nanoparticles for Peripheral Nerve Regeneration

Abstract: Peripheral nerve injury is a common clinical problem bringing heavy burden to patients, due to its high incidence and unsatisfactory treatment. Nerve guidance conduit (NGC) is a promising scaffold for peripheral nerve repair, and bioactive agents are applied for great functional recovery. Melatonin (MLT) and Fe3O4 magnetic nanoparticles (Fe3O4‐MNPs) are proven to inhibit oxidative stress, inflammation, and induce nerve regeneration. Herein, a multilayered composite NGC loaded with MLT and Fe3O4‐MNPs is designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 65 publications
(35 reference statements)
0
66
0
Order By: Relevance
“…(h) The release profile of MLT from both single-layered and multi-layered NGCs during the 21-day assessment. (c–h) Reproduced with permission [ 144 ]. Copyright 2021, John Wiley and Sons.…”
Section: Manufacturing and Functionalization Techniques For Ngcsmentioning
confidence: 99%
See 1 more Smart Citation
“…(h) The release profile of MLT from both single-layered and multi-layered NGCs during the 21-day assessment. (c–h) Reproduced with permission [ 144 ]. Copyright 2021, John Wiley and Sons.…”
Section: Manufacturing and Functionalization Techniques For Ngcsmentioning
confidence: 99%
“…One study reported a novel NGC based on electrospinning techniques with different solutions consists of three layers. The outer layer is made from PCL solution, the middle layer contains Fe 3 O 4 magnetic nanoparticles (Fe 3 O 4 -MNPs) in the previous PCL solution, while the inner layer solution is made up of Melatonin (MLT) instead of Fe 3 O 4 -MNPs [ 144 ]. The reason why Fe 3 O 4 -MNPs were chosen is that the magnetic nanoparticles have been reported to be able to induce the axonal extension under an external magnetic field without side effects [ 145 , 146 ].…”
Section: Manufacturing and Functionalization Techniques For Ngcsmentioning
confidence: 99%
“…The inhibition of excessive immune responses is of vital importance to restoring the balance in microenvironment after PNIs ( Qian et al, 2019b , 2020a , b ). The treatment of long-gap nerve defects requires highly functional biomimetic scaffolds to bridge the proximal and distal stumps ( Qian et al, 2019a , c ; Chen et al, 2020 ; Yan et al, 2020 ; Yang et al, 2020 ). In contrast, the treatment of severe nerve crush injuries relies more on the pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Application of magnetic field in responsive scaffolds have shown promising results for nerve regeneration 249 . The substantial effect of applied IONPs in nerve scaffolds was seen in terms of the axonal extension, increase in the neurite outgrowth, and activation of the signaling pathways of neuronal differentiation via direct interaction of SPIONs with proteins 248,249 . In another study, the multilayered composite NGC scaffold containing PCL, melatonin, and SPIONs also demonstrated axonal growth and prevention of inflammation 248 .…”
Section: Applicationsmentioning
confidence: 99%